Clinical effect of alpha-lipoic acid plus high flux hemodialysis on peripheral neuropathy in patients with diabetic hemodialysis - Shao Ning; Sun Zhi-hua; Huang Hao; Liu Lin-wei; Jin Wen-min; Zhang Shu-wei; Jiang Li-hua; Qiao Hong; Xie Hong-xia (Linchuang shenzangbing zazhi)
Objective To explore the clinical effect of alpha-lipoic acid plus high flux hemodialysis on diabetics with peripheral neuropathy.Methods A total of 60 patients with diabetic hemodialysis and peripheral neuropathy were selected from 2016 to 2019.They were randomly divided into control and observation groups.Control group received routine hemodialysis 3 times a week, 4 hours each time and took alpha-lipoic acid capsule, 1 capsule each time, 3 times daily; observation group was offered high flux hemodialysis treatment 3 times a week, 4 hours each time and also took alpha-lipoic acid capsule（same as control group）.Both groups were for 12 weeks.The clinical symptoms（limb pain, numbness & restless leg syndrome）,serum levels of oxidative stress index \[malondialdehyde（MDA）& advanced protein oxidation products（AOPP）\] and of serum parathyroid hormone（iPTH）,β2-microglobulin and peripheral nerves, sensory conduction velocity（median nerve, common peroneal nerve & tibial nerve）were compared between two groups before and after 12 weeks.Results After 12 weeks of treatment, clinical symptoms, oxidative stress parameters and nerve sensory conduction velocity markedly improved in both groups（P<0.05）and the improvement was more obvious in observation group than that in control group（P<0.05）.After dialysis, the levels of parathyroid hormone and β2-microglobulin were significantly lower in observation group than those in control group（P<0.05）.Conclusions Alpha-lipoic acid plus high flux hemodialysis can improve peripheral neuropathy in diabetic hemodialysis patients.